Recent advances in MDS mutation landscape: Splicing and signalling. (January 2020) - Follo, Matilde Y.; Pellagatti, Andrea; Ratti, Stefano; Ramazzotti, Giulia; Faenza, Irene; Fiume, Roberta; Mongiorgi, Sara; Suh, Pann-Ghill; McCubrey, James A.; Manzoli, Lucia; Boultwood, Jacqueline; Cocco, Lucio
Abstract: Recurrent cytogenetic aberrations, genetic mutations and variable gene expression have been consistently recognized in solid cancers and in leukaemia, including in Myelodysplastic Syndromes (MDS). Besides conventional cytogenetics, the growing accessibility of new techniques has led to a deeper analysis of the molecular significance of genetic variations. Indeed, gene mutations affecting splicing genes, as well as genes implicated in essential signalling pathways, play a pivotal role in MDS physiology and pathophysiology, representing potential new molecular targets for innovative therapeutic strategies.